Judicial Review: A Critical Study - Tripathy, Anwesha; Chaudhury, Maithili (International Journal of Psychosocial Rehabilitation, 2025)
The current research paper discusses the concept of judicial review and how it came to be originated with the case of Marbury v. Madison back in 1803. The paper also elucidates the various principles of natural justice before it talks about the various remedies that lie under the review such as certiorari, prohibition, habeas corpus, mandamus and quo warranto. The paper concludes with discussing the significance that judicial review holds in a democracy where the power can often go unfettered.